PICTORIAL STORY TOWARD THE STUDENTS’ ABILITY IN READING NARRATIVE TEXT IN SMP NEGERI 7 PADANGSIDIMPUAN - Rambe, Nana Ronawan (Lingue : Jurnal Bahasa, Budaya, dan Sastra, 2021)
bstract The factors that affect students' ability to read narrative text are motivation, teacher quality, infrastructure, teaching and teaching materials methods that use narrative text reading strategies. Class VIII students of SMP Negeri 7 Padangsidimpuan have low understanding in reading narrative text. This study aims to see the effect of using pictorial stories on students' ability to read narrative texts in class VIII of SMP Negeri 7 Padangsidimpuan. This research uses quantitative methods. Based on the results of the test analysis, it was found that the average number of students' ability to read narrative text before using the story was 79.5 and it was included in the "Good" category. The students' ability in reading narrative text after using the story was 82.75 and it was included in the "Very Good" category. After calculating and analyzing the data with the T-test, it was found that the T-observation was 2.518 and the t-table was 1.684 with a significant level of 5% (0.05). T observation is higher than T table (T0> Tt) (2.518> 1.684). This shows that there is a significant effect of the use of picture stories on the ability to read narrative text of students in class VIII SMP N 7 Padangsidimpuan. Keywords: Pictorial Story, Narrative Text